Analisis Putusan PTUN Terhadap Sengketa Kepegawaian Aparatur Sipil Negara (ASN) : Studi Kasus Mengenai Sengketa Mutasi, Pemberhentian, atau Disiplin ASN - Laila Nur Fadila; Pariwusiana Anwar; Anaku Alana; Muhammad Imam Syahid (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the decisions of the State Administrative Court (PTUN) regarding civil service disputes involving State Civil Apparatus (ASN), particularly those related to the rejection of ASN transfers (mutations). ASN employment disputes are a form of state administrative dispute that frequently occurs due to administrative decisions made by government officials that are considered to harm employees’ rights. This research uses a normative juridical method with statutory, case, and conceptual approaches. The legal materials used consist of primary legal sources in the form of legislation and PTUN decisions, as well as secondary legal materials such as books, journals, and other legal literature. The data collection technique is conducted through library research with descriptive-qualitative analysis. The results show that PTUN decisions play an important role in providing legal protection for ASN employees who are harmed by administrative decisions related to personnel transfers. In addition, judges’ considerations in resolving ASN employment disputes are based on aspects of authority, procedure, and the substance of state administrative decisions. This research is expected to contribute to the development of administrative law, particularly in relation to the settlement of ASN employment disputes in Indonesia.